A Study on the registration system of the Bureau of land Transportation (East Avenue, Quezon City) - Concepcion, Socorro O.; Fabic, John S.F; Ocreto, Ma. Josefina L.; Panis, Michael M.; Tan, Hera G. (College of Engineering, 1984)
One of the responsibilities of the Bureau of Land Transportation is the registration of motor vehicles. For the National Capital Region, two of the agencies entrusted with this task are the Pilot Agency and the Diliman Extension Office. The former takes care of registering for-hire motor vehicles and the latter is in charge of registering non-for-hire vehicles. The registration of motor vehicles, both new and renewal, plus the other transactions being handled by the agencies generally follow a fixed set of procedure. These include the ocular inspection of the vehicle, the confirmation of the franchise of the motor vehicle if it is classified as for-hire, the issuance of the official receipt and/or certificate of registration, the verification of the papers and the release of the sticker or plate. A problem of the present registration system is the unequal distribution of transactions during a given month since the registrants tend to register their motor vehicles during the last days of their scheduled registration month. Also, the Pilot Agency is the only authorized office to register for-hire motor vehicles plying in the Metro Manila area thus the system's "customers" is so huge in terms of number. This results in transactions being processed for a longer length of time. To help solve these existing problems, a design of a new registration system was made. The main features of this design include the delegation of the responsibility to determine whether a certain motor vehicle is fit for registration or not through an ocular inspection of the vehicles to authorized inspection-garages, the collection of fees will be done by the Philippine National Bank through its different branches and payment of the collectible fees will be made before the registrant enter the premises of the Pilot Agency or the Diliman Extension Office, and the creation of a discounting scheme to lure some of the registrants to register early during their scheduled month. With this proposed design, it is hoped that transactions will be distributed evenly during the month and the processing times for these transactions would be shortened. By successfully solving the two above-mentioned problems, the registration system will hopefully become more efficient and convenient for all parties concerned.